2016
DOI: 10.1111/peps.12142
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Cultural Intelligence: The Roles of Implicit Culture Beliefs and Adjustment

Abstract: Although international experience has been proposed as an important factor contributing to the development of cultural intelligence (CQ), its effect on CQ has often been assumed. Through a contact hypothesis framework, this study advances our understanding of CQ. It examines the process through which CQ changes occur against the backdrop of international exchanges. University students who were enrolled in an international exchange program with partners worldwide participated in this study. Using a 3‐wave time‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 96 publications
1
82
1
4
Order By: Relevance
“…The students demonstrated development of the cognitive-based components of the competence, and the study concluded that studying abroad can increase participants' motivational and behavioural cultural intelligence. Besides, Chao, Takeuchi, and Farh (2017) also commented that university students' implicit culture beliefs affected their intercultural rejection sensitivity, -which impacted the cross-cultural adjustment of sojourning students and their subsequent CQ‖ (p. 257). They, especially, discovered that cross-cultural adjustment experiences of joining an international exchange programme, in particular in the social dimension, are an important factor in influencing CQ performance.…”
Section: Cultural Intelligence (Cq) and Developing Cultural Competencementioning
confidence: 99%
“…The students demonstrated development of the cognitive-based components of the competence, and the study concluded that studying abroad can increase participants' motivational and behavioural cultural intelligence. Besides, Chao, Takeuchi, and Farh (2017) also commented that university students' implicit culture beliefs affected their intercultural rejection sensitivity, -which impacted the cross-cultural adjustment of sojourning students and their subsequent CQ‖ (p. 257). They, especially, discovered that cross-cultural adjustment experiences of joining an international exchange programme, in particular in the social dimension, are an important factor in influencing CQ performance.…”
Section: Cultural Intelligence (Cq) and Developing Cultural Competencementioning
confidence: 99%
“…In addition, in interracial interactions, individuals who endorse social constructionist (vs. essentialist) beliefs are more intrinsically interested in understanding and connecting with others from a different racial background (Chao, Takeuchi, & Farh, 2016;Yzerbyt, Rocher, & Schadron, 1997). Specifically, they were more motivated to gain acceptance by racial outgroups (Verkuyten, 2003;Verkuyten & Brug, 2004).…”
Section: Lay Theory Of Racementioning
confidence: 99%
“…Although race-related lay theories have drawn increasing research interest in the past two decades (Chao, Kung, & Yao, 2015;Chao et al, 2016;Keller, 2005;Levy, Plaks, Hong, Chiu, & Dweck, 2001;Levy, West, & Ramirez, 2005;Zagefka, Nigbur, Gonzalez, & Tip, 2013), no empirical work directly examines whether social constructionist (vs. essentialist) beliefs influence interracial trust. The current study bridges this gap.…”
Section: The Role Of Lay Theory Of Race In Interracial Trust and Coopmentioning
confidence: 99%
“…Antecedents (1) CQ (1) Relationship between international exposure, languages, orientations, sex, age, and education with BCIQ (Alon, Boulanger, Elston, Galanaki, de Ibarreta, Meyers et al, 2018) Learning (1) CQ (1) Experiential cross-cultural training and CQ (Alexandra, 2018) See also: Xu and Chen, 2017 (2) CC (1) Examine the mediating role of CC in the relationship between personality and cultural adjustment (Wu and Bodigerel-Koehler, 2013) Examine the relationship between CQ and transformational leadership (Ramsey et al, 2017) Examine the relationship between metacognitive and motivational CQ with cultural learning and job creativity of expatriates (Xu and Chen, 2017; see learning) * Group-level Outcome (2) CQ (2) Examine the moderating role of motivational CQ in the relationship between psychic distance and team performance (Magnusson et al, 2014) Examine the interaction effect between cognitive and metacognitive CQ on an individual's creativity in multicultural teams (Chua and Ng, 2017) CQ and international exposure (2D: 9) Concept, stages, measurement (1) CQ (1) Assessment of the cross-cultural equivalence of the four-dimensional 20-item CQ scale and the two-dimensional 12-item CQ short scale (Bücker et al, 2016) See also: Schreuders-van den Bergh and Du Plessis, 2016;Varela and Gatlin-Watts, 2014 Antecedents (4) CQ (4) Examine the relationship between cultural beliefs and CQ in international sojourns (Chao et al, 2017) Examine the relationship between international sojourns and CQ (Varela and Gatlin-Watts, 2014; see conceptualisation) * Examine the relationship between cross-cultural trigger events and CQ with a discussion of the implications for training (Reichard et al, 2015; see learning) * Examine the relationship between individual motives and CQ in study abroad programs and the mediating role of cultural boundary spanning (Holtbrügge and Engelhard, 2016) See also: Remhof et al, 2013 Learning See also:…”
Section: Individuallevel Outcomementioning
confidence: 99%